Absence of glucose-stimulated transport in yeast protoplasts - Kotyk, A; Michaljanicová, D; Struzinský, R; Baryshnikova, L M; Sychrová, H (Folia microbiologica, 1985)
Protoplasts of Saccharomyces cerevisiae prepared by snail-gut juice treatment were compared in their transport properties with intact cells. 1. Constitutive monosaccharide transport (D-xylose, 6-deoxy-D-glucose), as well as inducible transport of D-galactose, were unaltered. 2. Phosphorylation-associated transport of 2-deoxy-D-glucose was enhanced in protoplasts, possibly as a consequence of removal of the unstirred layer of the cell wall. 3. Proton-driven transports of trehalose, L-leucine, L-proline and monophosphate could not be activated by preincubation with D-glucose, apparently owing to lack of proton-solute coupling in transport. Utilization of glucose was not depressed but respiration was reduced by about 50% while acidification of the external medium after glucose addition was inhibited by more than 90%. This may be related to the inability of protoplast plasma membrane H-ATPase to be activated by glucose and hence to impaired proton-translocating capacity. Uranyl ions inhibited generally much less in protoplasts than in intact cells although their binding to protoplasts was greater (maximum 0.68 fmol per cell but 3.2 fmol per protoplast).
Keywords: Biological Transport; Protoplasts; Saccharomyces cerevisiae; biologický transport; Ethanol; protoplasty; glukosa; Monosaccharides; Carrier Proteins; ethanol; monosacharidy; proteiny přenášející monosacharidy; Monosaccharide Transport Proteins; transportní proteiny; Proton-Translocating ATPases; protonové ATPasy; Glucose